2017
DOI: 10.1017/s2045796017000774
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine contacts by persons with mental disorders in 25 countries: results from the World Mental Health Surveys

Abstract: CAM contacts are common in persons with severe mental disorders, in high-income countries, and in persons receiving conventional care. Our findings support the notion of CAM as largely complementary but are in contrast to suggestions that this concerns person with only mild, transient complaints. There was no indication that persons were less satisfied by CAM visits than by receiving conventional care. We encourage health care professionals in conventional settings to openly discuss the care patients are recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 36 publications
3
44
1
Order By: Relevance
“…This is about four times the proportion of CAM users who had no mental disorder. While the relatively higher proportion of CAM users among those who met the criteria for a mental disorder (compared with those who did not) is consistent with other studies which found the same pattern, the rates of CAM use found in this study differed from those found in other studies [9,18,30]. This may be attributed to the different definitions and criteria used pertaining to CAM use and the mental disorders identified in the studies.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This is about four times the proportion of CAM users who had no mental disorder. While the relatively higher proportion of CAM users among those who met the criteria for a mental disorder (compared with those who did not) is consistent with other studies which found the same pattern, the rates of CAM use found in this study differed from those found in other studies [9,18,30]. This may be attributed to the different definitions and criteria used pertaining to CAM use and the mental disorders identified in the studies.…”
Section: Discussionsupporting
confidence: 84%
“…general population [8]. In another study involving participants from 25 countries, CAM usage was reported by a total of 3.6% of respondents who met the criteria for a mental disorder as specified in the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition within the past 12 months, with increased prevalence in higher-income countries as opposed to lower-income countries [9].…”
mentioning
confidence: 99%
“…Mental disorders are the strongest contributor to disability worldwide. 1 The four major mental disorders that can lead to disability are major depression, bipolar disorder, schizophrenia, and obsessive-compulsive disorder (OCD). The incidence of mental disorders is high-in the United States, where 25 percent of US adults have been diagnosed with at least one mental disorder.…”
Section: Introductionmentioning
confidence: 99%
“…However, these drugs are not always effective and may cause serious adverse reactions. 1,2 Many mental disorder patients often take dietary supplements as an alternative treatment strategy. 5 Therefore, learning what type of dietary supplements that mental disorder patients usually take and how these dietary supplements affect their daily life is an important first step for both patients and their providers toward adequate treatments and management of their mental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with SRED frequently try complementary and alternative medicine (CAM), often because of dissatisfaction with conventional treatment options (Outram, Murphy, & Cockburn, 2004). A recent study in 25 countries reported that patients with severe mental disorders are satisfied after treatment with CAM (de Jonge et al, 2017) and that, compared with conventional therapies, CAM therapies are used more than expected by people with severe anxiety and depression and severe behavioral disorders (Hunt et al, 2010;Kessler et al, 2001).…”
Section: Introductionmentioning
confidence: 99%